ROLE OF SYSTEMIC MEDICATIONS IN ORAL CANCER PROGRESSION-A REVIEW - PAUL, PRIYANKA; BABU , N. ARAVINDHA; MALATHI , L.; MASTHAN , K.M.K.; R , DEEPIKA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Oral cancer encompasses malignancies within the oral cavity, including the lips, tongue, and other surrounding tissues. Systemic medications play crucial roles throughout the stages of oral cancer progression, ranging from prevention to palliative care. This review explores the various systemic treatment modalities, their mechanisms of action, and future perspectives on drug delivery systems designed for oral cancer management.